Economic composition of local government expenditure and regional welfare in East Java, Indonesia, 2021–2024 - Rafi'i, Rafi'i; Solihin, Achmad (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2026)
This study examines the relationship between the economic composition of local government expenditure and regional welfare outcomes across the districts and municipalities of East Java during the COVID-19 pandemic and post-pandemic recovery period (2021–2024). Using a balanced panel dataset comprising 38 local governments observed over four years (152 observations), the analysis employs Random Effects and Fixed Effects panel models with standard errors clustered at the district/municipality level to account for heteroskedasticity and within-panel error correlation. The results indicate that a higher capital expenditure share, relative to the omitted expenditure categories, is negatively and significantly associated with the poverty rate at the 5% significance level. Local own-source revenue (PAD) is also negatively and significantly associated with poverty, while the Human Development Index (HDI) exhibits the strongest conditional association with poverty. For consumption inequality, measured by the BPS Gini ratio, personnel expenditure share shows only a weak negative association under the fixed-effects specification, significant at the 10% level but not at the 5% level (p = 0.098). The relatively low within-R² of the Gini model (0.091) indicates that the economic composition of local government expenditure explains only a limited share of the variation in consumption inequality, suggesting that additional structural, spatial, and measurement-related factors not included in the model may explain part of the remaining variation. These findings contribute to the literature on fiscal federalism and public expenditure effectiveness by providing subnational evidence from a developing economy during the COVID-19 pandemic and post-pandemic recovery period.